MOTIVASI KERJA GURU MADRASAH (Studi Kasus pada Guru Madrasah Ibtidaiyyah di Kota Semarang) - Al Ansori, Afif; Yuniawan, Ahyar (Diponegoro Journal of Management, 2015)
Teacher is one of important component to determine the success of education program. Having a very important role to teach, teacher also has a huge responsibility towards the formation of character and morality of the students. Therefore, teachers are required to have expertise, responsibility and the spirit of sacrifice to provide a social service above personal interests. But, amid the many demands and duties of teachers, many problems experienced by teachers, particularly private teachers, especially around issues of welfare and employment status.This study was conducted to identify factors that motivate private teachers in their profession as well as to dig deeper about the hopes and desires of private teachers about their future. Search on the factors that motivate the private teacher starts from the identification of personal characteristics, biography and work values held by private teachers and their perceptions of the profession in which they live. This study uses a qualitative method and data collection was done by interview and observation so as to dig deeper into the facts about the teaching profession. The object of this research is a private teacher who has a service life of more than 2 years who served in Madrasah Ibtidaiyyah in Semarang City.The results showed that motivation of private teacher is influenced by their perception about teaching profession which is formed from the values they hold, personal characteristics and the biography of the informant.